Fabrication of Mesoporous‐Silica‐Coated Upconverting Nanoparticles with Ultrafast Photosensitizer Loading and 808 nm NIR‐Light‐Triggering Capability for Photodynamic Therapy. Issue 17 (3rd August 2017) - Han, Renlu; Shi, Junhui; Liu, Zongjun; Wang, Hao; Wang, You
Abstract: A novel photodynamic therapy nanoplatform based on mesoporous‐silica‐coated upconverting nanoparticles (UCNP) with electrostatic‐driven ultrafast photosensitizer (PS) loading and 808 nm near infrared (NIR)‐light‐triggering capabilities has been fabricated. By positively charging inner channels of the mesoporous silica shell with amino groups, a quantitative dosage of negatively charged PS, exemplified with Rose Bengal (RB) molecules, can be loaded in 2 min. In addition, the electrostatic‐driven technique simultaneously provides the platform with both excellent PS dispersity and leak‐proof properties due to the repulsion between the same‐charged molecules and the electrostatic attraction between different‐charged PS and silica channel walls, respectively. The as‐coated silica shell with an ultrathin thickness of 12±2 nm is delicately fabricated to facilitate ultrafast PS loading and efficient energy transfer from UCNP to PS. The outside surface of the silica shell is capped with hydrophilic β‐cyclodextrin, which not only enhances the dispersion of resulting nanoparticles in water but also plays a role of "gatekeeper", blocking the pore opening and preventing PS leaking. The in vitro cellular lethality experiment demonstrates that RB molecules can be activated to effectively generate singlet oxygen and kill cancer cells upon 808 nm NIR light irradiation. Abstract : A novel photodynamic therapy nanoplatform based on mesoporous‐silica‐coated upconverting nanoparticles with electrostatic‐driven ultrafast photosensitizer loading and 808 nm NIR‐light‐triggering capability was fabricated. The in vitro cellular uptake and low cell lethality of these nanoparticles demonstrate the nanoplatform is promising for low‐heat and high‐efficiency cancer theranostics.